Reporting, handling and assessing the risk of bias associated with missing participant data in systematic reviews: a methodological survey. Issue 9 (30th September 2015) - Akl, Elie A; Carrasco-Labra, Alonso; Brignardello-Petersen, Romina; Neumann, Ignacio; Johnston, Bradley C; Sun, Xin; Briel, Matthias; Busse, Jason W; Ebrahim, Shanil; Granados, Carlos E; Iorio, Alfonso; Irfan, Affan; et al.
Abstract : Objectives: To describe how systematic reviewers are reporting missing data for dichotomous outcomes, handling them in the analysis and assessing the risk of associated bias. Methods: We searched MEDLINE and the Cochrane Database of Systematic Reviews for systematic reviews of randomised trials published in 2010, and reporting a meta-analysis of a dichotomous outcome. We randomly selected 98 Cochrane and 104 non-Cochrane systematic reviews. Teams of 2 reviewers selected eligible studies and abstracted data independently and in duplicate using standardised, piloted forms with accompanying instructions. We conducted regression analyses to explore factors associated with using complete case analysis and with judging the risk of bias associated with missing participant data. Results: Of Cochrane and non-Cochrane reviews, 47% and 7% (p<0.0001), respectively, reported on the number of participants with missing data, and 41% and 9% reported a plan for handling missing categorical data. The 2 most reported approaches for handling missing data were complete case analysis (8.5%, out of the 202 reviews) and assuming no participants with missing data had the event (4%). The use of complete case analysis was associated only with Cochrane reviews (relative to non-Cochrane: OR=7.25; 95% CI 1.58 to 33.3, p=0.01). 65% of reviews assessed risk of bias associated with missing data; this was associated with Cochrane reviews (relative to non-Cochrane: OR=6.63; 95% CI 2.50 to 17.57, p=0.0001), and the use of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology (OR=5.02; 95% CI 1.02 to 24.75, p=0.047). Conclusions: Though Cochrane reviews are somewhat less problematic, most Cochrane and non-Cochrane systematic reviews fail to adequately report and handle missing data, potentially resulting in misleading judgements regarding risk of bias.